Α-Tocopherol supplementation reduces 5-nitro-γ-tocopherol accumulation by decreasing γ-tocopherol in young adult smokers*. (September 2015) - Pei, R.; Mah, E.; Leonard, S. W.; Traber, M. G.; Bruno, R. S.
Abstract γ-Tocopherol (γ-T) scavenges reactive nitrogen species (RNS) to form 5-NO2-γ-T (NGT). However, α-T supplementation decreases circulating γ-T, which could limit its RNS scavenging activities. We hypothesized that α-T supplementation would mitigate NGT accumulation by impairing γ-T status. Healthy smokers (21 ± 1 y, n = 11) and non-smokers (21 ± 2 y, n = 10) ingested 75 mg/d each of RRR- and all-rac-α-tocopheryl acetate for 6 d. Plasma α-T, γ-T, γ-carboxyethyl hydroxychromanol (CEHC), NGT, and nitrate/nitrite were measured prior to supplementation (Pre), the morning after 6 consecutive evenings of supplementation (Post 1), and on the mornings of d 6 (Post 6) and d 14 (Post 14) during the post-supplementation period. α-T supplementation increased plasma α-T, and decreased γ-T, in both groups and these returned to Pre concentrations on Post 6 regardless of smoking status. Plasma γ-CEHC increased after the first dose of supplementation in both groups, suggesting that α-T supplementation decreased plasma γ-T in part by increasing its metabolism. Plasma NGT and nitrate/nitrite concentrations at Pre were greater in smokers, indicating greater nitrative stress due to cigarette smoking. Plasma NGT concentration was lowered only in smokers on Post 1 and Post 6 and was restored to Pre levels on Post 14. Plasma nitrate/nitrite tended (P = 0.07) to increase post-supplementation only in smokers, supporting decreases in RNS scavenging by γ-T. Plasma NGT concentration was more strongly correlated (P < 0.05) with γ-T in smokers (R = 0.83) compared with non-smokers (R = 0.50), supporting that α-T-mediated decreases in γ-T reduces NGT formation. These data indicate that α-T supplementation limits γ-T scavenging of RNS in smokers by decreasing γ-T availability.